Rozciąganie Silami Skupionymi Tarczy Nieograniczonej z Otworem Kołowym / Rozciąganie Silami Skupionymi Tarczy Nieograniczonej z Ośrodkiem Sztywnym Zarysu Kołowego - Szelągowski, F. (Engineering Transactions, 1956)
The stresses Ro, R, and 09 at any point of an infinite plate having a circular hole of radius R and subjected to tension by two concentrated forces P acting at the distances a from the centre of the hole are determined by Eqs. (11), (12) and (13), respectively. The equations under consideration are valid only for values of a contained in the interval R